Determination of the absolute configuration of chaetoviridins and other bioactive azaphilones from the endophytic fungus Chaetomium globosum. Issue 21 (1st November 2015) - Youn, Ui Joung; Sripisut, Tawanun; Park, Eun-Jung; Kondratyuk, Tamara P.; Fatima, Nighat; Simmons, Charles J.; Wall, Marisa M.; Sun, Dianqing; Pezzuto, John M.; Chang, Leng Chee
Graphical abstract